Rare case of adult Xanthogranuloma: a case report - Hasan, Fatima; Najia Ahmed (Journal of the Pakistan Medical Association, 2023)
Xanthogranulomas are the most common form of non-Langerhans cell histiocytosis. They are benign, asymptomatic, and self-healing, affecting mostly infants, children, and very rarely adults. They present clinically as erythematous to yellow-brown papules. In children they can be single to multiple but in adults they are solitary. We present the case of a 23-year-old Pakistani man with an erythematous to yellow-brown papule on his neck that persisted for 1.5 years. The results of an excision biopsy showed histopathological features of histiocytes, tuoton giant cells and necrobiosis corresponding to xanthogranuloma. We emphasize the importance of considering xanthogranuloma in skin coloured nodules. Keywords: Xanthoma, Non-Langerhan cell histiocytosis, Skin tumour.